Efficiency and Power Consumption of Aspiration Systems at Woodworking Plants - P. I. Diachek (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper analyzes present state of the equipment and organization of aspiration at wood-working shops. Proposals pertaining to higher efficiency and reduction of power intensity of aspiration systems are given in the paper. Materials presented at the stage of designing make it possible to select a rational system scheme and reduce power expenditure at woodworking industry.